Solid electrolyte material, battery using same, and method for producing solid electrolyte material
By adopting solid electrolyte materials composed of Li, DC, Y, Sm and X, combined with specific composition ratios and manufacturing processes, the composition deviation and safety of solid electrolyte materials in the prior art at high temperatures is solved, and a solid electrolyte material with high ionic conductivity and safety is achieved.
Patent Information
- Application Number
- JP2022511604
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-31
- Filing Date
- 2021-02-05
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2041-02-05
AI Technical Summary
In the prior art, solid electrolyte materials tend to cause composition deviations and reduced conductivity at high temperatures, and some solid electrolyte materials will generate toxic gases when they come into contact with air, affecting safety.
Solid electrolyte materials composed of Li, DC, Y, Sm and X are used, where DC selects Ca, X selects Cl and Br, and through specific compositional proportions and manufacturing processes, the ionic conductivity and chemical stability of the material are improved, and the use of sulfides is avoided to reduce the generation of toxic gases.
The high ionic conductivity and good charging and discharging performance of solid electrolyte materials are achieved, while improving the safety of the materials and avoiding the generation of toxic gases.
Smart Images

Figure 0007664539000005 
Figure 0007664539000006 
Figure 0007664539000007
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid electrolyte material, a battery using the same, and a method for manufacturing the solid electrolyte material.
Background Art
[0002] Patent Document 1 discloses an all-solid-state battery using a sulfide solid electrolyte.
[0003] Patent Document 2 discloses a solid electrolyte material represented by the composition formula Li 6-3z Y z X6 (0 < z < 2, X = Cl or Br).
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Patent Document 2
Summary of the Invention
Problems to be Solved by the Invention
[0005] An object of the present disclosure is to provide a novel solid electrolyte material with high utility.
Means for Solving the Problems
[0006] The solid electrolyte material of the present disclosure contains Li, DC, Y, Sm, and X, DC is at least one selected from the group consisting of Mg, Ca, Sr, Ba, and Zn, X is at least one selected from the group consisting of F, Cl, Br, and I.
Effects of the Invention
[0007] The present disclosure provides a novel solid electrolyte material with high utility. [Brief description of the drawings]
[0008] [Figure 1] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment. [Diagram 2] FIG. 2 is a flowchart showing an example of a manufacturing method according to the third embodiment. [Diagram 3] FIG. 3 is a flowchart showing an example of a manufacturing method according to the third embodiment. [Figure 4] FIG. 4 is a flowchart showing an example of a manufacturing method according to the third embodiment. [Diagram 5] FIG. 5 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of a solid electrolyte material. [Figure 6] FIG. 6 is a graph showing a Cole-Cole plot obtained by impedance measurement of the solid electrolyte material according to Example 1. [Figure 7] FIG. 7 is a graph showing the X-ray diffraction patterns according to Examples 1 to 6, Examples 10 to 15, Comparative Example 1, and Comparative Example 2. [Figure 8] FIG. 8 is a graph showing the X-ray diffraction patterns according to Examples 7 to 9, Comparative Example 1, and Comparative Example 2. [Figure 9] FIG. 9 is a graph showing the initial discharge characteristics of the battery according to Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.
[0010] (First embodiment) The solid electrolyte material according to the first embodiment includes Li, DC, Y, Sm, and X. DC is at least one selected from the group consisting of Mg, Ca, Sr, Ba, and Zn. X is at least one selected from the group consisting of F, Cl, Br, and I.
[0011] The solid electrolyte material according to the first embodiment can have, for example, a practical lithium ion conductivity, for example, a high lithium ion conductivity. Here, the high lithium ion conductivity is, for example, 1×10 -5 That is, the solid electrolyte material according to the first embodiment has a dielectric constant of, for example, 1×10 -5 The ionic conductivity may be 1.0 S / cm or more.
[0012] The solid electrolyte material according to the first embodiment can be used to obtain a battery having excellent charge / discharge characteristics. An example of the battery is an all-solid-state battery. The all-solid-state battery may be a primary battery or a secondary battery.
[0013] It is desirable that the solid electrolyte material according to the first embodiment does not substantially contain sulfur. The solid electrolyte material according to the first embodiment does not substantially contain sulfur means that the solid electrolyte material does not contain sulfur as a constituent element, except for sulfur that is inevitably mixed in as an impurity. In this case, the amount of sulfur mixed in the solid electrolyte material as an impurity is, for example, 1 mol % or less. It is more desirable that the solid electrolyte material according to the first embodiment does not contain sulfur. A solid electrolyte material that does not contain sulfur is excellent in safety because hydrogen sulfide is not generated even when exposed to the atmosphere. The sulfide solid electrolyte disclosed in Patent Document 1 may generate hydrogen sulfide when exposed to the atmosphere.
[0014] In order to enhance the ionic conductivity of the solid electrolyte material, the solid electrolyte material according to the first embodiment may be substantially composed of Li, DC, Y, Sm, and X. Here, "the solid electrolyte material according to the first embodiment is substantially composed of Li, DC, Y, Sm, and X" means that the ratio (i.e., the molar fraction) of the total amount of substance of Li, DC, Y, Sm, and X to the total amount of substance of all elements constituting the solid electrolyte material according to the first embodiment is 90% or more. As an example, the ratio may be 95% or more. The solid electrolyte material according to the first embodiment may be composed only of Li, DC, Y, Sm, and X.
[0015] The solid electrolyte material according to the first embodiment may contain elements that are inevitably mixed in. Examples of such elements are hydrogen, oxygen, or nitrogen. Such elements may be present in the raw material powder of the solid electrolyte material or in the atmosphere for producing or storing the solid electrolyte material.
[0016] In order to enhance the ionic conductivity of the solid electrolyte material, X may be at least one selected from the group consisting of Cl and Br.
[0017] To increase the ionic conductivity of the solid electrolyte material, the DC may be Ca.
[0018] The solid electrolyte material according to the first embodiment may be a material represented by the following composition formula (1). Li 3-2a-3d DC a Y 1-b Sm b+d Br 6-c Cl c (1) Here are the four formulas: 0 <a≦0.25、 0 <b<1、 0≦c≦6, and 0≦d≦0.05, The material represented by the composition formula (1) has high ionic conductivity.
[0019] In order to enhance the ionic conductivity of the solid electrolyte material, the formula: 0.01≦a≦0.15 may be satisfied in composition formula (1).
[0020] In order to enhance the ionic conductivity of the solid electrolyte material, the formula: 0.01≦b≦0.5 may be satisfied in composition formula (1).
[0021] In order to enhance the ionic conductivity of the solid electrolyte material, the formula: 1.5≦c≦2.5 may be satisfied in composition formula (1).
[0022] The upper and lower limit values of the range of a in the compositional formula (1) may be defined by any combination selected from numerical values greater than 0 (i.e., 0 < a), 0.01, 0.1, 0.15, 0.125, 0.15, and 0.25.
[0023] The upper and lower limit values of the range of b in the compositional formula (1) may be defined by any combination selected from numerical values greater than 0 and less than 1 (i.e., b < 1), 0.01, 0.1, 0.15, 0.2, 0.3, 0.5, 0.7, 0.9.
[0024] The upper and lower limit values of the range of c in the compositional formula (1) may be defined by any combination selected from the numerical values 0, 1.5, 2.5, 3, 3.5, 4, 4.5, 5, and 6.
[0025] The X-ray diffraction pattern of the solid electrolyte material in the first embodiment can be obtained by X-ray diffraction measurement using the θ-2θ method with Cu-Kα rays (wavelengths 1.5405 Å and 1.5444 Å, i.e., wavelengths 0.15405 nm and 0.15444 nm). In the obtained X-ray diffraction pattern, there may be at least one peak in the range of diffraction angle 2θ of 29.0° or more and 32.0° or less, and at least two peaks in the range of diffraction angle 2θ of 14.0° or more and 18.0° or less. The crystal phase having such peaks is called the first crystal phase. The solid electrolyte material containing the first crystal phase has high ionic conductivity. When the solid electrolyte material contains the first crystal phase, a path for lithium ions to diffuse is easily formed. Therefore, the ionic conductivity is further improved.
[0026] The first crystal phase belongs to the trigonal system. The crystal phase belonging to the trigonal system has a crystal structure similar to Li3ErCl6 disclosed in the ICSD (Inorganic Crystal Structure Database) Collection Code 50151 and has an X-ray diffraction pattern characteristic of this structure.
[0027] In the X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα radiation, at least two peaks may be present in the range of diffraction angle 2θ of 24.0° or more and 35.0° or less, and at least one peak may be present in the range of diffraction angle 2θ of 12.0° or more and 16.0° or less. A crystal phase having such peaks is called a second crystal phase. A solid electrolyte material containing the second crystal phase has high ionic conductivity. When the solid electrolyte material contains the second crystal phase, a path for lithium ion diffusion is easily formed. Therefore, the ionic conductivity is further improved. In the above X-ray diffraction pattern, the second crystal phase may have at least two peaks in the range of diffraction angle 2θ of 26.0° or more and 35.0° or less, and at least one peak in the range of diffraction angle 2θ of 13.7° or more and 16.0° or less. Such a solid electrolyte material has a higher ionic conductivity. When the solid electrolyte material contains a crystal phase having the above peak, a path for lithium ion diffusion is more easily formed. Therefore, the ionic conductivity is further improved.
[0028] The second crystal phase belongs to a monoclinic system. The crystal phase belonging to the monoclinic system has a crystal structure similar to Li3ErBr6 disclosed in ICSD (Inorganic Crystal Structure Database) Collection Code 50182, and has an X-ray diffraction pattern specific to this structure.
[0029] The solid electrolyte material according to the first embodiment may further contain a third crystal phase different from the first crystal phase and the second crystal phase. That is, the solid electrolyte material according to the first embodiment may further contain a third crystal phase having a peak outside the range of the diffraction angle 2θ described above. The third crystal phase may be interposed between the first crystal phase and the second crystal phase.
[0030] The solid electrolyte material according to the first embodiment may be crystalline or amorphous.
[0031] The shape of the solid electrolyte material according to the first embodiment is not limited. Examples of the shape are needle-like, spherical, or elliptical. The solid electrolyte material according to the first embodiment may be particles. The solid electrolyte material according to the first embodiment may be formed to have a pellet or plate shape.
[0032] When the shape of the solid electrolyte material according to the first embodiment is, for example, particulate (for example, spherical), the solid electrolyte material may have a median diameter of 0.1 μm or more and 100 μm or less. The median diameter means a particle size when the cumulative volume in the volume-based particle size distribution is equal to 50%. The volume-based particle size distribution is measured, for example, by a laser diffraction measuring device or an image analyzing device.
[0033] The solid electrolyte material according to the first embodiment may have a median diameter of 0.5 μm or more and 10 μm or less. This allows the solid electrolyte material according to the first embodiment to have higher ion conductivity. Furthermore, when the solid electrolyte material according to the first embodiment is mixed with other materials such as active materials, the solid electrolyte material according to the first embodiment and the other materials are well dispersed.
[0034] Second embodiment The second embodiment will be described below. The matters described in the first embodiment may be omitted.
[0035] The battery according to the second embodiment includes a positive electrode, a negative electrode, and an electrolyte layer. The electrolyte layer is provided between the positive electrode and the negative electrode. At least one selected from the group consisting of the positive electrode, the electrolyte layer, and the negative electrode contains the solid electrolyte material according to the first embodiment.
[0036] The battery according to the second embodiment has excellent charge / discharge characteristics because it contains the solid electrolyte material according to the first embodiment. The battery may be an all-solid-state battery.
[0037] FIG. 1 shows a cross-sectional view of a battery 1000 according to a second embodiment.
[0038] The battery 1000 according to the second embodiment includes a positive electrode 201, an electrolyte layer 202, and a negative electrode 203. The electrolyte layer 202 is provided between the positive electrode 201 and the negative electrode 203.
[0039] The positive electrode 201 contains positive electrode active material particles 204 and solid electrolyte particles 100 .
[0040] The electrolyte layer 202 contains an electrolyte material, for example, a solid electrolyte material.
[0041] The negative electrode 203 contains negative electrode active material particles 205 and solid electrolyte particles 100 .
[0042] The solid electrolyte particle 100 is a particle made of the solid electrolyte material according to the first embodiment, or a particle containing the solid electrolyte material according to the first embodiment as a main component. Here, the particle containing the solid electrolyte material according to the first embodiment as a main component means a particle in which the component contained most abundantly in terms of molar ratio is the solid electrolyte material according to the first embodiment.
[0043] The positive electrode 201 contains a material capable of absorbing and releasing metal ions (for example, lithium ions). The material is, for example, a positive electrode active material (for example, positive electrode active material particles 204).
[0044] Examples of the positive electrode active material are lithium-containing transition metal oxides, transition metal fluorides, polyanion materials, fluorinated polyanion materials, transition metal sulfides, transition metal oxyfluorides, transition metal oxysulfides, or transition metal oxynitrides. Examples of lithium-containing transition metal oxides are Li(Ni,Co,Al)O2 or LiCoO2. In this disclosure, the notation "(Ni,Co,Al)" in the chemical formula represents at least one selected from the group of elements in parentheses. That is, "(Ni,Co,Al)" means "at least one selected from the group consisting of Ni, Co, and Al". The same applies to other elements.
[0045] The positive electrode active material particles 204 may have a median diameter of 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 204 have a median diameter of 0.1 μm or more, the positive electrode active material particles 204 and the solid electrolyte particles 100 are well dispersed in the positive electrode 201. This improves the charge / discharge characteristics of the battery. When the positive electrode active material particles 204 have a median diameter of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 is improved. This allows the battery to operate at high power.
[0046] The positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100. This allows the positive electrode active material particles 204 and the solid electrolyte particles 100 to be well dispersed in the positive electrode 201.
[0047] From the viewpoint of the energy density and output of the battery, in the positive electrode 201, the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0048] From the viewpoint of the energy density and output of the battery, the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.
[0049] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, the solid electrolyte material according to the first embodiment. The electrolyte layer 202 may be a solid electrolyte layer.
[0050] The electrolyte layer 202 may be made of only the solid electrolyte material according to the first embodiment. Alternatively, the electrolyte layer 202 may be made of only a solid electrolyte material different from the solid electrolyte material according to the first embodiment.
[0051] Examples of solid electrolyte materials different from the solid electrolyte material according to the first embodiment are Li2MgX'4, Li2FeX'4, Li(Al,Ga,In)X'4, Li3(Al,Ga,In)X'6, or LiI, where X' is at least one selected from the group consisting of F, Cl, Br, and I.
[0052] Hereinafter, the solid electrolyte material according to the first embodiment will be referred to as a first solid electrolyte material, and a solid electrolyte material different from the solid electrolyte material according to the first embodiment will be referred to as a second solid electrolyte material.
[0053] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed in the electrolyte layer 202. A layer made of the first solid electrolyte material and a layer made of the second solid electrolyte material may be stacked along the stacking direction of the battery 1000.
[0054] The electrolyte layer 202 may have a thickness of 1 μm or more and 1000 μm or less. When the electrolyte layer 202 has a thickness of 1 μm or more, the positive electrode 201 and the negative electrode 203 are less likely to short-circuit. When the electrolyte layer 202 has a thickness of 1000 μm or less, the battery can operate at high output.
[0055] The negative electrode 203 contains a material capable of absorbing and releasing metal ions such as lithium ions. The material is, for example, a negative electrode active material (for example, negative electrode active material particles 205).
[0056] Examples of the negative electrode active material are metal materials, carbon materials, oxides, nitrides, tin compounds, or silicides. The metal material may be a single metal or an alloy. Examples of the metal material are lithium metal or lithium alloys. Examples of the carbon material are natural graphite, coke, partially graphitized carbon, carbon fiber, spherical carbon, artificial graphite, or amorphous carbon. From the viewpoint of capacity density, suitable examples of the negative electrode active material are silicon (i.e., Si), tin (i.e., Sn), silicides, or tin compounds.
[0057] The negative electrode active material particles 205 may have a median diameter of 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 205 have a median diameter of 0.1 μm or more, the negative electrode active material particles 205 and the solid electrolyte particles 100 are well dispersed in the negative electrode 203. This improves the charge / discharge characteristics of the battery. When the negative electrode active material particles 205 have a median diameter of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 is improved. This allows the battery to operate at high power.
[0058] The negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100. This allows the negative electrode active material particles 205 and the solid electrolyte particles 100 to be well dispersed in the negative electrode 203.
[0059] From the viewpoint of the energy density and output of the battery, in the negative electrode 203, the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0060] From the viewpoint of energy density and output, the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.
[0061] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a second solid electrolyte material for the purpose of increasing ion conductivity, chemical stability, and electrochemical stability.
[0062] As mentioned above, the second solid electrolyte material may be a halide solid electrolyte.
[0063] Examples of halide solid electrolytes are Li2MgX'4, Li2FeX'4, Li(Al,Ga,In)X'4, Li3(Al,Ga,In)X'6, or LiI, where X' is at least one selected from the group consisting of F, Cl, Br, and I.
[0064] The second solid electrolyte material may be a sulfide solid electrolyte.
[0065] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4, or Li 10 GeP2S 12 It is.
[0066] The second solid electrolyte material may be an oxide solid electrolyte.
[0067] Examples of oxide solid electrolytes include: (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or elemental substitutions thereof; (ii) Perovskite-type solid electrolytes such as (LaLi)TiO3; (iii) Li 14 ZnGeO 16 LISICON-type solid electrolytes such as Li4SiO4, LiGeO4 or elemental substitutes thereof; (iv) Li7La3Zr2O 12 or a garnet-type solid electrolyte such as an elemental substitution product thereof; or (v) Li3PO4 or its N-substituted derivatives It is.
[0068] The second solid electrolyte material may be an organic polymer solid electrolyte.
[0069] Examples of organic polymer solid electrolytes include polymer compounds and lithium salt compounds. The polymer compounds may have an ethylene oxide structure. Polymer compounds having an ethylene oxide structure can contain a large amount of lithium salt, and therefore can further increase ion conductivity.
[0070] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.
[0071] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a nonaqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the exchange of lithium ions and improving the output characteristics of the battery.
[0072] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent.
[0073] Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents, or fluorine solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate, or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate, or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane, or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorine solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, fluoroethyl methyl carbonate, or fluorodimethylene carbonate. One type of non-aqueous solvent selected from these may be used alone, or a mixture of two or more types of non-aqueous solvents selected from these may be used.
[0074] Examples of the lithium salt are LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), or LiC(SO2CF3)3. One type of lithium salt selected from these may be used alone. Alternatively, a mixture of two or more types of lithium salts selected from these may be used. The concentration of the lithium salt is, for example, 0.5 mol / liter or more and 2 mol / liter or less.
[0075] The gel electrolyte may be a polymer material impregnated with a non-aqueous electrolyte, such as polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.
[0076] Examples of cations contained in ionic liquids are: (i) Aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium salts; (ii) aliphatic cyclic ammonium such as pyrrolidiniums, morpholiniums, imidazoliniums, tetrahydropyrimidiniums, piperaziniums, or piperidiniums, or (iii) nitrogen-containing heterocyclic aromatic cations such as pyridinium or imidazolium It is.
[0077] An example of an anion contained in an ionic liquid is PF6 - , BF4 - , SbF6 - , AsF6 - , SO3CF3 - , N(SO2CF3)2 - , N(SO2C2F5)2 - , N(SO2CF3)(SO2C4F9) - , or C(SO2CF3)3 - It is.
[0078] The ionic liquid may contain a lithium salt.
[0079] At least one selected from the group consisting of the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may contain a binder for the purpose of improving adhesion between particles.
[0080] Examples of binders are polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polyacrylic acid methyl ester, polyacrylic acid ethyl ester, polyacrylic acid hexyl ester, polymethacrylic acid, polymethacrylic acid methyl ester, polymethacrylic acid ethyl ester, polymethacrylic acid hexyl ester, polyvinyl acetate, polyvinylpyrrolidone, polyether, polyethersulfone, hexafluoropolypropylene, styrene butadiene rubber, or carboxymethylcellulose. Copolymers may also be used as binders. Examples of such binders are copolymers of two or more materials selected from the group consisting of tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, and hexadiene. A mixture of two or more materials selected from the above materials may be used as a binder.
[0081] At least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive assistant for the purpose of increasing electronic conductivity.
[0082] Examples of the conductive additive include: (i) Graphites, such as natural or synthetic graphite; (ii) Carbon blacks such as acetylene black or ketjen black; (iii) Conductive fibers, such as carbon or metal fibers; (iv) fluorocarbons; (v) Metal powders such as aluminium; (vi) conductive whiskers such as zinc oxide or potassium titanate; (vii) a conductive metal oxide, such as titanium dioxide; or (viii) Conductive polymers such as polyaniline, polypyrrole, or polythiophene In order to reduce costs, the above-mentioned conductive assistant (i) or (ii) may be used.
[0083] Examples of the shape of the battery according to the second embodiment are a coin type, a cylindrical type, a square type, a sheet type, a button type, a flat type, or a laminate type.
[0084] The battery according to the second embodiment may be manufactured, for example, by preparing a material for forming a positive electrode, a material for forming an electrolyte layer, and a material for forming a negative electrode, and producing a laminate in which the positive electrode, the electrolyte layer, and the negative electrode are arranged in this order by a known method.
[0085] Third embodiment The third embodiment will be described below. The matters described in the first and second embodiments may be omitted as appropriate.
[0086] FIG. 2 is a flowchart showing an example of a manufacturing method according to the third embodiment.
[0087] The manufacturing method according to the third embodiment includes a firing step S1000. In the firing step S1000, the mixed material is fired in an inert gas atmosphere.
[0088] The mixed material to be fired in the firing step S1000 includes a halide containing Li, a halide containing Y, a halide containing Sm, and a halide containing DC, where DC is at least one selected from the group consisting of Mg, Ca, Sr, and Ba.
[0089] The manufacturing method according to the third embodiment can manufacture the solid electrolyte material according to the first embodiment. The manufacturing method according to the third embodiment is a method with high industrial productivity. An industrially highly productive method is, for example, a method that can be mass-produced at low cost. That is, the manufacturing method according to the third embodiment can manufacture a solid electrolyte material containing Li, DC, Y, and Sm by a simple manufacturing method, that is, by firing in an inert gas atmosphere, without using a vacuum sealed tube and a planetary ball mill.
[0090] In the firing step S1000, powder of the mixed material may be placed in a container (eg, a crucible) and fired in a heating furnace.
[0091] The mixed material may be sintered at 200°C or more and 650°C or less. This allows the solid electrolyte material to be produced by a highly productive method. By setting the sintering temperature to 200°C or more, the mixed material can be sufficiently reacted. By setting the sintering temperature to 650°C or less, composition deviation due to thermal decomposition of the mixed material and the solid electrolyte material produced by the solid-phase reaction can be suppressed.
[0092] In order to produce a solid electrolyte material having higher ion conductivity by an industrially highly productive method, the mixed material may be sintered at 400° C. or more and 650° C. or less. By setting the sintering temperature to 400° C. or more, the mixed material can be sufficiently reacted.
[0093] In order to produce a solid electrolyte material having higher ionic conductivity by an industrially highly productive method, the mixed material may be sintered at 450° C. or higher (for example, 450° C. or higher and 650° C. or lower). This allows the sintered product (i.e., the produced solid electrolyte material) to have higher crystallinity. As a result, the ionic conductivity of the produced solid electrolyte material can be further increased. In other words, a better quality solid electrolyte material can be obtained.
[0094] In order to produce a solid electrolyte material having higher ionic conductivity by an industrially highly productive method, the mixed material may be sintered at 550°C or lower (for example, 400°C or higher and 550°C or lower, or 450°C or higher and 550°C or lower). 550°C or lower is a temperature below the melting point of a halide such as LiBr or LiI. Therefore, by setting the sintering temperature to 550°C or lower, it is possible to suppress the composition deviation of the sintered product caused by the volatilization of the halide. As a result, it is possible to suppress the decrease in the ionic conductivity of the sintered product (i.e., the solid electrolyte material produced). In other words, a good quality solid electrolyte material is obtained.
[0095] The mixed material may be sintered for 1 minute or more and 9000 minutes or less, thereby enabling the solid electrolyte material to be produced by a method with high industrial productivity.
[0096] When the firing temperature is 400° C. or higher, the mixed material may be fired for 1 minute or more and 3600 minutes or less. This allows the solid electrolyte material to be produced by an industrially highly productive method. By setting the firing time to 1 minute or more, the mixed material can be sufficiently reacted. By setting the firing time to 3600 minutes or less, volatilization of the fired material can be suppressed. That is, a solid electrolyte material having a target composition ratio or a composition close to the target can be obtained. As a result, a decrease in the ionic conductivity of the solid electrolyte material caused by a composition deviation can be suppressed. That is, a better quality solid electrolyte material can be obtained.
[0097] In order to produce a solid electrolyte material having higher ionic conductivity by an industrially highly productive method, the mixed material may be fired for 180 minutes or less (for example, 1 minute or more and 180 minutes or less). By setting the firing time to 180 minutes or less, volatilization of the fired solid electrolyte material can be further suppressed. As a result, a solid electrolyte material having a target composition ratio or a composition close to the target can be obtained (i.e., composition deviation can be further suppressed). As a result, a decrease in the ionic conductivity of the fired product (i.e., the produced solid electrolyte material) can be suppressed. In other words, a better quality solid electrolyte material can be obtained.
[0098] The inert gas may be, for example, helium, nitrogen, or argon.
[0099] After the firing step S1000, the fired product may be taken out of the container (e.g., crucible) and pulverized using a pulverizing tool (e.g., a mortar or mixer).
[0100] The mixed material may be a material in which Liα, Yβ3, Smγ3, and DCδ2 are mixed, where α, β, γ, and δ are each independently at least one selected from the group consisting of F, Cl, Br, and I. This allows a solid electrolyte material containing Li, DC, Y, and Sm to be easily produced.
[0101] Liα, Yβ3, Smγ3, and DCδ2 may be mixed in a molar ratio of, for example, LiBr:LiCl:DCCl2:YCl3:SmCl3=2:0.8:0.1:0.8:0.2. 2.8 Ca 0.1 Y 0.8 Sm 0.2 A solid electrolyte material can be produced having a composition represented by Br2Cl4.
[0102] The mixed material may be not only Liα, Yβ3, Smγ3, and DCδ2, but also a material in which a material different from Liα, Yβ3, Smγ3, and DCδ2 is further mixed.
[0103] The mixed material is further e X f may be a material in which M is mixed. Here, M is at least one selected from the group consisting of Na, K, In, Sn, Bi, La, Ce, Pr, Nd, Pm, Gd, Eu, Tb, Dy, Ho, Er, Tm, Yb, and Lu. X is at least one selected from the group consisting of F, Cl, Br, and I. e>0 and f>0 are satisfied. This can improve the properties (e.g., ionic conductivity) of the manufactured solid electrolyte material.
[0104] The above M e X f In this case, e=1 and 1≦f≦5 may be satisfied.
[0105] Each of α, β, γ, and δ may be independently at least one selected from the group consisting of Cl and Br, which can further improve the properties (e.g., ionic conductivity) of the produced solid electrolyte material.
[0106] At least one selected from the group consisting of Liα, Yβ3, Smγ3, and DCδ2 contained in the mixed material may have a portion of the cations (i.e., Li, Y, Sm, and DC) replaced by another cation (e.g., M as described above).
[0107] FIG. 3 is a flowchart showing an example of a manufacturing method according to the third embodiment.
[0108] As shown in FIG. 3, the manufacturing method according to the third embodiment may further include a mixing step S1100.
[0109] The mixing step S1100 is performed before the firing step S1000.
[0110] In the mixing step S1100, a halide containing Li, a halide containing Y, a halide containing Sm, and a halide containing DC, which are raw materials of the solid electrolyte material, are mixed together to obtain a mixed material (i.e., a material to be fired in the firing step S1000).
[0111] In the mixing step S1100, a halide containing Li, a halide containing Y, a halide containing Sm, and a halide containing DC may be prepared and mixed in a desired molar ratio. A known mixing tool (e.g., a mortar, a blender, or a ball mill) may be used to mix the raw materials.
[0112] In the mixing step S1100, powders of the respective raw materials may be prepared and mixed. At this time, in the firing step S1000, the powdered mixed material may be fired. The powdered mixed material obtained in the mixing step S1100 may be molded into a pellet shape by pressing. Alternatively, in the firing step S1000, the pelletized mixed material may be fired.
[0113] In the mixing step S1100, for example, Liα, Yβ3, Smγ3, and DCδ2 are mixed. Here, α, β, γ, and δ are each independently at least one selected from the group consisting of F, Cl, Br, and I.
[0114] In the mixing step S1100, in addition to Liα, Yβ3, Smγ3, and DCδ2, a raw material different from Liα, Yβ3, Smγ3, and DCδ2 (for example, the above-mentioned M e X f etc.) may be further mixed to obtain a mixed material.
[0115] In the mixing step S1100, a raw material mainly composed of Liα, a raw material mainly composed of Yβ3, a raw material mainly composed of Smγ3, and a raw material mainly composed of DCδ2 may be mixed. The main component is the component that is contained in the largest amount by molar ratio.
[0116] FIG. 4 is a flowchart showing an example of a manufacturing method according to the third embodiment.
[0117] As shown in FIG. 4, the manufacturing method according to the third embodiment may further include a preparation step S1200.
[0118] The preparing step S1200 is performed before the mixing step S1100.
[0119] In the preparing step S1200, a halide containing Li, a halide containing Y, a halide containing Sm, and a halide containing DC (ie, the materials to be mixed in the mixing step S1100) are prepared.
[0120] In the preparation step S1200, for example, Liα, Yβ3, Smγ3, and DCδ2 are prepared. Here, α, β, γ, and δ are each independently at least one selected from the group consisting of F, Cl, Br, and I.
[0121] In the preparation step S1200, a material such as Liα, Yβ3, Smγ3, or DCδ2 may be synthesized. Alternatively, in the preparation step S1200, a known commercially available product (for example, a material with a purity of 99% or more) may be used.
[0122] The material provided may be dry.
[0123] Examples of the shape of the prepared material include crystal, lump, flake, or powder. In the preparation step S1200, a powdered raw material may be obtained by pulverizing a crystal, lump, or flake raw material.
[0124] In the preparation step S1200, the above-mentioned M e X f may be added, which can improve the properties (e.g., ion conductivity, etc.) of the produced solid electrolyte material.
[0125] At least one selected from the group consisting of Liα, Yβ3, Smγ3, and DCδ2 to be prepared may have some of the cations (i.e., Li, Y, Sm, and DC) replaced by another cation (e.g., M as described above). EXAMPLES
[0126] Hereinafter, the present disclosure will be described in more detail with reference to examples and comparative examples.
[0127] <Example 1> (Preparation of solid electrolyte materials) In an argon atmosphere having a dew point of -60°C or less (hereinafter referred to as "dry argon atmosphere"), LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2:0.8:0.1:0.8:0.2. These raw material powders were ground and mixed in an agate mortar. The obtained mixed powder was placed in an alumina crucible and fired at 500°C for 60 minutes in a dry argon atmosphere. The obtained fired product was ground in the agate mortar. In this manner, a powder of the solid electrolyte material according to Example 1 was obtained. The solid electrolyte material according to Example 1 was composed of Li 2.8 Ca 0.1 Y 0.8 Sm 0.2 The composition was determined to be Br2Cl4.
[0128] (Evaluation of ionic conductivity) FIG. 5 shows a schematic diagram of a pressing die 300 used to evaluate the ionic conductivity of the solid electrolyte material.
[0129] The pressure molding die 300 had an upper punch 301, a frame 302, and a lower punch 303. The upper punch 301 and the lower punch 303 were both made of electronically conductive stainless steel. The frame 302 was made of insulating polycarbonate.
[0130] Using the pressure molding die 300 shown in FIG. 5, the ionic conductivity of the solid electrolyte material according to Example 1 was evaluated by the following method.
[0131] In a dry atmosphere having a dew point of -60°C or less, the powder of the solid electrolyte material according to Example 1 was filled into the inside of the pressure molding die 300. In the inside of the pressure molding die 300, a pressure of 360 MPa was applied to the solid electrolyte material according to Example 1 using the upper punch 301 and the lower punch 303.
[0132] While the pressure was still applied, the upper punch 301 and the lower punch 303 were connected to a potentiostat (Princeton Applied Research, VersaSTAT4) equipped with a frequency response analyzer. The upper punch 301 was connected to a working electrode and a terminal for measuring potential. The lower punch 303 was connected to a counter electrode and a reference electrode. The impedance of the solid electrolyte material was measured by electrochemical impedance measurement at room temperature.
[0133] FIG. 6 is a graph showing a Cole-Cole plot obtained by impedance measurement of the solid electrolyte material according to Example 1.
[0134] In FIG. 6, the real value of the impedance at the measurement point where the absolute value of the phase of the complex impedance is the smallest was considered to be the resistance value for the ion conduction of the solid electrolyte material. The real value is indicated by the arrow R SE Using the resistance value, the ionic conductivity was calculated based on the following formula (2). σ = (R SE ×S / t) -1 (2) Here, σ represents ion conductivity. S represents the contact area of the solid electrolyte material with the punch upper portion 301. In other words, S is equal to the cross-sectional area of the hollow portion of the frame mold 302 in FIG. 5. R SE represents the resistance value of the solid electrolyte material in the impedance measurement. t represents the thickness of the solid electrolyte material. That is, t is equal to the thickness of the layer formed from the powder 101 of the solid electrolyte material in FIG.
[0135] The ionic conductivity of the solid electrolyte material according to Example 1 measured at 24° C. was 2.86×10 -3 S / cm.
[0136] (X-ray diffraction measurement) Fig. 7 is a graph showing the X-ray diffraction pattern of the solid electrolyte material of Example 1. The results shown in Fig. 7 were measured by the following method.
[0137] The X-ray diffraction pattern of the solid electrolyte material according to Example 1 was measured using an X-ray diffractometer (MiniFlex600, Rigaku) in a dry environment with a dew point of -50°C or less. The X-ray diffraction pattern was measured by the θ-2θ method using Cu-Kα radiation (wavelengths 1.5405 Å and 1.5444 Å) as the X-ray source.
[0138] In the X-ray diffraction pattern of the solid electrolyte material of Example 1, one peak was present in the range of 29.0° or more and 32.0° or less, and two peaks were present in the range of 14.0° or more and 18.0° or less.
[0139] (Battery Construction) In a dry argon atmosphere, the solid electrolyte material according to Example 1 and LiCoO2 were prepared in a volume ratio of 30:70. These materials were mixed in a mortar. In this way, a mixture was obtained.
[0140] In an insulating cylinder having an inner diameter of 9.5 mm, the solid electrolyte material according to Example 1 (80 mg) and the above mixture (10 mg) were laminated in this order. A pressure of 720 MPa was applied to the resulting laminate, and a solid electrolyte layer formed from the solid electrolyte material according to Example 1 and a first electrode formed from the above mixture were formed. The solid electrolyte layer had a thickness of 600 μm.
[0141] Next, metal In (thickness 200 μm), metal Li (thickness 200 μm), and metal In (thickness 200 μm) were laminated in this order on the solid electrolyte layer. A pressure of 80 MPa was applied to the resulting laminate to form a second electrode.
[0142] Next, current collectors made of stainless steel were attached to the first and second electrodes, and current collecting leads were attached to the current collectors.
[0143] Finally, the inside of the insulating cylinder was isolated from the outside atmosphere by using an insulating ferrule, and the inside of the cylinder was sealed. In this manner, the battery according to Example 1 was obtained.
[0144] (Charge / discharge test) 9 is a graph showing the initial discharge characteristics of the battery according to Example 1. The initial charge / discharge characteristics were measured by the following method.
[0145] The battery according to Example 1 was placed in a thermostatic chamber at 25°C.
[0146] 78μA / cm 2 The battery according to Example 1 was charged until a voltage of 3.68 V was reached at a current density of 0.05 C, which corresponds to a 0.05 C rate.
[0147] Next, 78 μA / cm 2 The battery according to Example 1 was discharged at a current density of 0.1 V until a voltage of 1.88 V was reached.
[0148] As a result of the charge / discharge test, the battery according to Example 1 had an initial discharge capacity of 1.2 mAh.
[0149] <Examples 2 to 46> (Preparation of solid electrolyte materials) In Example 2, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2:0.8:0.1:0.9:0.1.
[0150] In Example 3, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2:0.8:0.1:0.7:0.3.
[0151] In Example 4, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2:0.8:0.1:0.5:0.5.
[0152] In Example 5, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2:0.8:0.1:0.3:0.7.
[0153] In Example 6, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2:0.8:0.1:0.1:0.9.
[0154] In Example 7, LiBr, CaBr2, YBr3, and SmBr3 were prepared as raw material powders in a molar ratio of LiBr:CaBr2:YBr3:SmBr3=2.8:0.1:0.8:0.2.
[0155] In Example 8, the raw material powder was LiBr, CaBr 2, YCl3, and SmCl3 were prepared in a molar ratio of LiBr:CaBr2:YCl3:SmCl3=2.8:0.1:0.8:0.2.
[0156] In Example 9, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2.5:0.3:0.1:0.8:0.2.
[0157] In Example 10, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=1.5:1.3:0.1:0.8:0.2.
[0158] In Example 11, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=1:1.8:0.1:0.8:0.2.
[0159] In Example 12, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiCl:CaCl2:YCl3:SmCl3=2.8:0.1:0.8:0.2.
[0160] In Example 13, the raw material powder was LiBr, Ca Br 2, YCl3, and SmCl3 were prepared in a molar ratio of LiBr:CaBr2:YCl3:SmCl3=2.8:0.1:0.9:0.1.
[0161] In Example 14, LiBr, CaBr2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:CaBr2:YCl3:SmCl3=2.8:0.1:0.1:0.9.
[0162] In Example 15, LiBr, CaBr2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:CaBr2:YCl3:SmCl3=2.7:0.15:0.9:0.1.
[0163] In Example 16, LiBr, CaBr2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:CaBr2:YCl3:SmCl3=2.7:0.15:0.1:0.9.
[0164] In Example 17, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2:0.75:0.125:0.8:0.2. In Example 17, the firing time was 180 minutes.
[0165] In Example 18, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2:0.7:0.15:0.8:0.2. In Example 18, the firing time was 180 minutes.
[0166] In Example 19, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2:0.5:0.25:0.8:0.2. In Example 19, the firing time was 180 minutes.
[0167] In Example 20, LiBr, LiCl, MgCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:MgCl2:YCl3:SmCl3=2:0.8:0.1:0.8:0.2.
[0168] In Example 21, LiBr, LiCl, SrCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:SrCl2:YCl3:SmCl3=2:0.8:0.1:0.8:0.2.
[0169] In Example 22, LiBr, LiCl, BaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:BaCl2:YCl3:SmCl3=2:0.8:0.1:0.8:0.2.
[0170] In Example 23, LiBr, LiCl, ZnCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:ZnCl2:YCl3:SmCl3=2:0.8:0.1:0.8:0.2.
[0171] In Example 24, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2:0.65:0.1:0.85:0.2.
[0172] In Example 25, LiBr, LiCl, CaCl2, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:YCl3:SmCl3=2:0.65:0.1:0.9:0.15.
[0173] Except for the above, the solid electrolyte materials according to Examples 2 to 25 were obtained in the same manner as in Example 1.
[0174] In Examples 26 to 46, except for the firing time and temperature, the solid electrolyte materials according to Examples 26 to 46 were obtained in the same manner as in Example 1. The firing temperature and firing time are shown in Table 1-2.
[0175] (Evaluation of ionic conductivity) The ionic conductivity of the solid electrolyte materials according to Examples 2 to 46 was measured in the same manner as in Example 1. The measurement results are shown in Tables 1-1 and 1-2.
[0176] (X-ray diffraction measurement) The X-ray diffraction patterns of the solid electrolyte materials according to Examples 2 to 19 were measured in the same manner as in Example 1.
[0177] Figure 7 is a graph showing the X-ray diffraction patterns of the solid electrolyte materials according to Examples 1 to 6, 10 to 12, 14, and 16 to 19. The angles of the observed diffraction peaks are shown in Table 2-1. All of the solid electrolyte materials shown in Figure 7 had a first crystal phase.
[0178] FIG. 8 is a graph showing the X-ray diffraction patterns of the solid electrolyte materials according to Examples 7 to 9, 13, and 15. The angles of the observed diffraction peaks are shown in Table 2-2. All of the solid electrolyte materials shown in FIG. 8 had a second crystal phase. Examples 8, 9, and 15 had not only the second crystal phase but also the first crystal phase.
[0179] (Charge / discharge test) Using the solid electrolyte materials according to Examples 2 to 46, batteries according to Examples 2 to 46 were obtained in the same manner as in Example 1. Using the batteries according to Examples 2 to 46, charge / discharge tests were carried out in the same manner as in Example 1. As a result, the batteries according to Examples 2 to 46 were successfully charged and discharged, similar to the battery according to Example 1.
[0180] <Comparative Examples 1 and 2> (Preparation of solid electrolyte materials) In Comparative Example 1, LiBr, LiCl, CaCl2, and SmCl3 were prepared as raw material powders in a molar ratio of LiBr:LiCl:CaCl2:SmCl3=2:0.8:0.1:1. Other than this, the solid electrolyte material according to Comparative Example 1 was obtained in the same manner as in Example 1.
[0181] In Comparative Example 2, LiCl, YCl3, and SmCl3 were prepared as raw material powders in a molar ratio of LiCl:YCl3:SmCl3=3:0.1:0.9. Other than this, the solid electrolyte material according to Comparative Example 2 was obtained in the same manner as in Example 1.
[0182] (Evaluation of ionic conductivity) The ionic conductivity of the solid electrolyte materials according to Comparative Examples 1 and 2 was measured in the same manner as in Example 1. The measurement results are shown in Table 1-2.
[0183] (X-ray diffraction measurement) The X-ray diffraction patterns of the solid electrolyte materials according to Comparative Examples 1 and 2 were measured in the same manner as in Example 1. Figures 7 and 8 are graphs showing the X-ray diffraction patterns of the solid electrolyte materials according to Comparative Examples 1 and 2. The angles of the observed diffraction peaks are shown in Tables 2-1 and 2-2.
[0184] [Table 1-1]
[0185] [Table 1-2]
[0186] [Table 2-1]
[0187] [Table 2-2]
[0188] <Consideration> The solid electrolyte materials according to Examples 1 to 46 had a melting point of 1×10 -5 It has a higher ionic conductivity of more than S / cm.
[0189] As is apparent from Examples 17 to 19 and 32, when the value of a is 0.1 or more and 0.25 or less, the solid electrolyte material has high ionic conductivity. As is apparent from comparing Examples 17, 18, and 32 with Example 19, when the value of a is 0.1 or more and 0.15 or less, the solid electrolyte material has higher ionic conductivity.
[0190] As is apparent from Examples 1 to 46, when the value of b is 0.1 or more and 0.9 or less, the solid electrolyte material has high ionic conductivity. As is apparent from comparing Examples 1 to 4 with Examples 5 and 6, when the value of b is 0.1 or more and 0.5 or less, the solid electrolyte material has even higher ionic conductivity.
[0191] As is clear from a comparison of Examples 1, 9, and 10 with Examples 7, 8, 11, and 12, when the value of c is 3.5 or more and 4.5 or less, the solid electrolyte material has high ionic conductivity.
[0192] As is clear from Examples 1, 16, and 17, when DC is at least one selected from the group consisting of Ca, Mg, and Sr, the solid electrolyte material has high ionic conductivity. As is clear from comparing Example 1 with Examples 16 and 17, when DC is Ca, the solid electrolyte material has higher ionic conductivity.
[0193] As is clear from Examples 1, 18, and 19, when the value of d is 0 or more and 0.05 or less, the solid electrolyte material has high ionic conductivity.
[0194] In all Examples 1 to 46, the cells were charged and discharged at room temperature.
[0195] As is clear from comparing Examples 1, 26 to 28, 35, 40, and 42 with Example 44, if the firing temperature is 450°C or more and 650°C or less, the solid electrolyte material has a higher ion conductivity. This is believed to be because the solid electrolyte material has a higher crystallinity. As is clear from comparing Examples 1, 26 to 28, 35, and 40 with Examples 26 and 27, if the firing temperature is 450°C or more and 550°C or less, the solid electrolyte material has an even higher ion conductivity. This is believed to be because the occurrence of thermal decomposition at high temperatures, that is, the occurrence of composition deviation of the solid electrolyte material, can be suppressed.
[0196] As is clear from a comparison of Examples 1 and 29 to 32 with Examples 33 and 34, when the firing time is 1 minute or more and 180 minutes or less, the solid electrolyte material has a higher ionic conductivity. This is considered to be because thermal decomposition (i.e., composition deviation of the solid electrolyte material) caused by long-term firing can be suppressed.
[0197] The solid electrolyte materials according to Examples 1 to 46 do not contain sulfur and therefore do not generate hydrogen sulfide.
[0198] As described above, the solid electrolyte material according to the present disclosure is suitable for providing a battery having high lithium ion conductivity and capable of being charged and discharged well. Furthermore, the method for producing the solid electrolyte material according to the present disclosure is a method with high industrial productivity that can easily produce a solid electrolyte material having high ion conductivity. [Industrial Applicability]
[0199] The solid electrolyte material and the method for producing the same according to the present disclosure are used, for example, in batteries (for example, all-solid-state lithium ion secondary batteries).
Claims
1. Li, DC, Y, Sm, and X; DC is at least one selected from the group consisting of Mg, Ca, Sr, Ba, and Zn; X is at least one selected from the group consisting of Cl and Br; Represented by the following composition formula (1): Li 3-2a-3d DC a Y 1-b Sm b+d Br 6-c Cl c...(1) Here, the following four formulas: 0<a≦0.25, 0<b<1, 0≦c≦6, and 0≦d≦0.05 is satisfied; Solid electrolyte material.
2. DC is Ca The solid electrolyte material according to claim 1 .
3. The formula: 0.01≦a≦0.15 is satisfied; The solid electrolyte material according to claim 1 or 2.
4. The formula: 0.01≦b≦0.5 is satisfied; The solid electrolyte material according to claim 1 .
5. The formula: 3.5≦c≦4.5 is satisfied; The solid electrolyte material according to claim 1 .
6. In an X-ray diffraction pattern obtained by X-ray diffraction measurement of the solid electrolyte material using Cu-Kα radiation, at least one peak is present in a diffraction angle 2θ range of 29.0° or more and 32.0° or less, and at least two peaks are present in a diffraction angle 2θ range of 14.0° or more and 18.0° or less. The solid electrolyte material according to claim 1 .
7. In an X-ray diffraction pattern obtained by X-ray diffraction measurement of the solid electrolyte material using Cu-Kα radiation, at least two peaks are present in a diffraction angle 2θ range of 24.0° or more and 35.0° or less, and at least one peak is present in a diffraction angle 2θ range of 12.0° or more and 16.0° or less. The solid electrolyte material according to claim 1 .
8. In the X-ray diffraction pattern, at least two peaks are present in a diffraction angle 2θ range of 26.0° or more and 35.0° or less, and at least one peak is present in a diffraction angle 2θ range of 13.7° or more and 16.0° or less. The solid electrolyte material according to claim 7.
9. positive electrode, a negative electrode, and an electrolyte layer provided between the positive electrode and the negative electrode; Equipped with At least one selected from the group consisting of the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 8. battery.
10. A method for producing a solid electrolyte material according to any one of claims 1 to 8, comprising the steps of: The method includes a firing step of firing a mixed material containing a halide containing Li, a halide containing Y, a halide containing Sm, and a halide containing DC under an inert gas atmosphere; DC is at least one selected from the group consisting of Mg, Ca, Sr, and Ba; A method for producing a solid electrolyte material.
11. In the firing step, the mixed material is fired at 200° C. or more and 650° C. or less. The method of claim 10.
12. The mixed material is Liα, Yβ 3 , Smγ 3 , and DCδ 2 is a mixed material, α, β, γ, and δ are each independently at least one selected from the group consisting of Cl and Br; The method according to claim 10 or 11.
Citation Information
Patent Citations
Metal composite oxide with novel crystal structure and its use as ion conductor
JP2007531682A
Method of manufacturing sulfide solid electrolyte material, sulfide solid electrolyte material, and lithium battery
JP2011129312A
Phosphor, its preparation method and light emitting devices using the same
US20090050918A1
Solid electrolyte material, and cell
WO2018025582A1
Solid electrolyte material, and battery
WO2019135343A1